Normal Reflection and Transmission of Plane Shock Waves in Nonlinear Elastic Material - Kosiński, S. (Engineering Transactions, 1986)
The normal reflection (reflection and transmission) of a finite elastic plane shock wave at a plane boundary (plane interface of two rigidly coupled materials), propagating through an elastic Murnaghan’s material is examined. Tt is assumed that the materiał region in front of the shock wave is homogeneously strained and at rest. The linearized boundary value problem is considered for analysing small but finite amplitude waves. Three types of boundary conditions are considered. The obtained reflection solution is one shock wave, simple wave or progressive wave, when the only transmitted wave is always the shock wave.